Alterações comportamentais e metabólicas induzidas pelo estilo de vida: ação do disseleneto de m-trifluormetil-difenila em camundongos - Müller, Sabrina Grendene (2023)
Modern lifestyle is composed of unhealthy habits, including energy-dense food and ethanol intake. The increase in these habits has been related to depression, anxiety, and obesity. Besides, pharmacological approaches are needed to treat lifestyle-related diseases. m-Trifluoromethyldiphenyl diselenide [(m-CF3-PhSe)2] is a low-toxicity compound with pharmacological properties, including anti-inflammatory, antidepressive- and anxiolytic-like in animal models. This thesis aimed to evaluate (m-CF3-PhSe)2 effects on depressive and anxiolytic-like phenotypes and markers of metabolism of carbohydrates and lipids in young mice exposed to a lifestyle model: association of an energy-dense diet and ethanol sporadic intake. Firstly, for article 1, article 2 and article 3 25 days old Swiss male mice (CEUA: 7141061018 e 4849060420) were exposed to an energy-dense diet until postnatal day 66. From the postnatal day 45 to 60, the animals received, by the intragastric (i.g) route, an ethanol sporadic regimen, 3 times a week at 2g/kg. Posteriorly, (m-CF3-PhSe)2 was administered via i.g. for 7 days. From postnatal days 67 to 68, some animals were subjected to behavioral tests predictive of depressive-like behavior (article 1), whereas others performed anxiety-like tests (article 2). On day 69, the animals were euthanized and the cerebral cortex (article 1 and article 2), the liver, the blood, and the hypothalamus (article 3) were collected for analyses. The results of article 1 demonstrated that the modulation of the opioid system and the antioxidant effect in the cerebral cortex of mice contributed to the (m-CF3-PhSe)2 effectiveness in the lifestyle depression-induced model. In article 2, the results revealed that (m-CF3-PhSe)2 elicited an anxiolytic-like effect associated with the modulation of NMDAR-mediated neurotoxicity, neuroinflammation and by the improvement of synaptic plasticity in the cerebral cortex of mice exposed to the lifestyle model. Finally, (m-CF3-PhSe)2 reversed the accumulation of relative abdominal white adipose tissue to body weight, which was accompanied by hepatic lipotoxicity (article 3). Furthermore, (m-CF3-PhSe)2 modulated glycolytic pathway markers, hepatic insulin signaling, and counteracted hypothalamic inflammation in young mice subjected to the lifestyle-induced model. Besides, in article 3, (m-CF3-PhSe)2 modulated hypothalamic insulin, ghrelin, and leptin receptor levels of mice exposed to the lifestyle model. The results of this thesis contributed to a better comprehension of (m-CF3-PhSe)2 action against depressive- and anxiety-like phenotypes and against the lipotoxicity, insulin signaling, and glycolytic pathway markers in the liver and the hypothalamic inflammation induced by the lifestyle model in young mice.